RESPONS ENAM VARIETAS CABAI (Capsicum annuum) TERHADAP HASIL, VIABILITAS, DAN VIGOR BENIH - Yenni Kusandriani; Uum Sumpena; Luthfi Luthfi (Universitas Lampung, 2013)
An experiment was carried out at the experimental Station and Seed technology laboratory of Central Research Institute for Vegetable Lembang, from June until November 2010. Randomized Block Design was used to study six varieties of pepper. The six varieties of pepper were: YK 1, YK 2, Tanjung 1, Tanjung 2, Rk1 and Rk4. The results showed that there was no significant effect among varieties on yield, seed viability and vigor, except on seedling vigor classification test. The Tanjung 2 was the best variety for seed weight per plot and normally for seedling vigor classification test. Key words: pepper, variety, seed, yield, viability, vigor.